Comparison of Inhibitory and Bactericidal Activities and Postantibiotic Effects of LY333328 and Ampicillin Used Singly and in Combination against Vancomycin-Resistant Enterococcus faecium - Baltch, Aldona L. (American Society for Microbiology, 1998)
One hundred ninety-five individual vancomycin-resistant Enterococcus faecium (VRE) isolates from five upstate New York hospitals were studied for antimicrobial susceptibilities to LY333328, quinupristin-dalfopristin, teicoplanin, ampicillin, and gentamicin. LY333328 was the most active antibiotic against VRE. The effect of media and methods on the antibacterial activity of LY333328, its synergy with ampicillin, and the postantibiotic effects (PAE) of LY333328 and ampicillin were evaluated. In microdilution tests, the MIC of LY333328 at which 90% of the isolates were inhibited (MIC(90)) was 2 μg/ml in Mueller-Hinton II (MH II) broth and 1 μg/ml in brain heart infusion (BHI) broth. In contrast, on MH II agar the MIC(90) was 4 μg/ml and on BHI agar it was >16 μg/ml. Bactericidal activity was observed for most strains at concentrations from 8 to ≥133 times the MIC of the tube macrodilution in MH II broth. A bactericidal effect of LY333328 plus ampicillin was demonstrated in time-kill studies, but there was great strain-to-strain variability. By the MH II agar dilution method, bacteristatic synergy (defined as a fractional inhibitory concentration of <0.5) with LY333328 and ampicillin was demonstrated for 61% of the strains tested. Under similar conditions, there was synergy with LY333328 and quinupristin-dalfopristin or gentamicin for 27 and 15% of the strains tested, respectively. The PAE of LY333328 was prolonged (23.0 h at 10 times the MIC). However, 50% normal pooled human serum decreased the PAE to 12.2 h at 10 times the MIC. Test conditions and media had a considerable effect on VRE susceptibilities to LY333328. The prolonged PAE of LY333328, a potent new bactericidal glycopeptide, and its synergy with ampicillin in a large proportion of strains suggest that further evaluation of this drug in pharmacokinetic studies and experimental infections, including those with VRE, is warranted.